Transcriptomic time course of skeletal muscle disuse and rehabilitation in middle‐aged adults - Von Ruff, Zachary D.; Kilroe, Sean P.; Marchant, Erik D.; Arentson‐Lantz, Emily J.; Widen, Steven; Thompson, Jill; Villasante‐Tezanos, Alejandro; Volpi, Elena; Paddon‐Jones, Doug; Rasmussen, Blake B. (Physiological reports, 2025)
Disuse drives rapid muscle atrophy and metabolic dysfunction. This study aimed to characterize phenotypic and transcriptomic skeletal muscle changes in middle‐aged individuals during disuse and rehabilitation. Eleven healthy middle‐aged adults (6 males, 5 females; age; 57 ± 5 years) underwent 7 days of unilateral lower limb suspension (ULLS). Following disuse, participants participated in a rehabilitation program consisting of either a lower‐body resistance exercise (RE) or walking control (WC) three times weekly for 2 weeks. Bilateral skeletal muscle biopsies were collected at Day 0 and Day 7 of disuse and 2 h post‐exercise on Days 7, 9, 11, and 21. Strength testing was conducted, and RNA sequencing was performed on muscle samples. Seven days of disuse reduced knee extension strength (14%; p < 0.05) and isometric force (13%; p < 0.05). Over‐representation analysis revealed a downregulation of mRNAs related to cellular respiration and NADH dehydrogenase complex assembly. Resistance exercise induced robust, but different, transcriptional changes in both disuse‐ and control‐legs. Walking had minimal effect on the muscle transcriptome. We conclude that 7 days of disuse reduced leg strength, decreased mitochondrial gene expression, and increased inflammation and apoptosis‐related genes. We also conclude that resistance exercise enhanced recovery from disuse by improving strength, associated with significant transcriptomic changes.